Dukungan Keluarga Dengan Depresi Pada Lansia - Weni Lidya Hendayani; Ridhyalla Afnuhazi (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2018)
According to WHO (World Health Organization) depression is the third largest psychological disorder that is thought to occur in (5%) of the world's population and the onset of depression has a relationship with several factors one of which is family support. The purpose of this study was to determine the relationship of family support with the level of depression in the elderly in the Social Home Tresna Werdha Kasih Sayang Batusangkar. This research use cross sectional approach. The study was conducted at the Tresna Werdha Social House of Mother Love Batusangkar in July 2017 with a population of 53 elderly people who suffer from depression. Sampling technique with total sampling. Data processing is done computerized using computerized program. The result of univariate analysis showed that (67,9%) respondents got good support and (39,6%) respondents had moderate depression. In bivariate analysis p value = 0.008 means there is a relationship of family support with depression level in elderly. It is expected that Tresna Werdha Social Welfare officer Kasih Ibu Batusangkar to raise awareness and always give support to elderly. It is intended that the level of depression in the elderly in the Social House Tresna Werdha Valentine's Love Batusangkar decreased even none.